Ethnic politics and public sector management in Trinidad and Guyana - Brown, Deryck R. (1999)
Representativeness and diversity in public institutions are among the principles of good and democratic governance, but a commitment to achieving `balance' is far easier said than done, particularly in the context of small, ethnically divided societies in which political mobilization is based on ethnic identity. Trinidad and Guyana are two such societies in which political power was held for a long time by a dominant ethnic group and has recently been transferred to the former `out group'. Specifically, politics in both territories was dominated by parties that are identified with the urban African populations, whereas the main opposition parties drew their electoral support almost exclusively from rural Indian groups. In both cases the Indian `out group' accused the African `in group' of favouring members of the latter group - and, conversely, of discriminating against the Indians - in the allocation of resources which are in the gift of the state. Also in both countries, democratic elections have resulted in regime changes after three decades of near one-party rule. The issue of employment in the public service has become critical as the two groups battle for scarce resources, and the public service is described as a `theatre of inter-ethnic drama'. The article takes the view that managing ethnic and cultural diversity is tantamount to managing unproductive tensions that threaten to undermine confidence and morale among public officials. This impacts negatively on their levels of job satisfaction, the quality of the work environment and, ultimately, on performance and output. It breeds suspicion among co-workers and has the potential to degenerate into ethnic strife that can cripple the public sector and affect the overall goal of national development. The article examines existing legal/constitutional and institutional provisions for conflict management and resolution, but ultimately suggests the need for well-conceived confidence-building measures such as public scrutiny of the personnel function and the reintroduction of ethnicity as a category on official government personnel records. The main theoretical conclusion is that while equality of opportunity must be guaranteed, the notion of a representative bureaucracy has many practical limitations that make it unworkable in Trinidad and Guyana. - Reproduced
Keywords: Bureaucracy - Guyana; Bureaucracy - Trinidad; Public administration